2021
DOI: 10.4103/ijdr.ijdr_943_20
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine- A New Treatment Option for Erosive Oral Lichen Planus

Abstract: Context: Oral Lichen planus (OLP) is a chronic, debilitating, immune-mediated disease whose management is considered a challenge in medical science. Aims: To quantitatively evaluate the effect of administration of enteral hydroxychloroquine (HCQS) as a monotherapy for six months on the extent and severity of erosive OLP using reticular score, erythema score and ulcerative score (REU score), and to subjectively evaluate the success of HCQS as a therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Recurrent episodes of autoimmune diseases are believed to be due, in part, to the persistence of local Trm cells that are difficult to eliminate entirely ( Jiang et al, 2012 ; Owczarczyk Saczonek et al, 2020 ). Immunosuppressive medications and local, or systemic corticosteroids are the main treatments for symptomatic OLP ( García-Pola et al, 2017 ; Raj et al, 2021 ). We discovered that there was no statistically significant difference between medication therapy and repeated degradation of OLP in our cohort analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent episodes of autoimmune diseases are believed to be due, in part, to the persistence of local Trm cells that are difficult to eliminate entirely ( Jiang et al, 2012 ; Owczarczyk Saczonek et al, 2020 ). Immunosuppressive medications and local, or systemic corticosteroids are the main treatments for symptomatic OLP ( García-Pola et al, 2017 ; Raj et al, 2021 ). We discovered that there was no statistically significant difference between medication therapy and repeated degradation of OLP in our cohort analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective clinical trial on 45 patients with erosive OLP, HCQ 200 mg p.o. twice daily as monotherapy was reported as effective and safe ( 59 ). In addition, Yeshurun et al reported a moderate to marked improvement in 57% and a complete remission in 24% patients with erosive OLP on HCQ 400 mg/day p.o.…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…The selection of dexamethasone as reference drug is due to its widely use and its status as first‐line drug to manage OLP (Carbone et al, 2003; Fu et al, 2012; Husein‐ElAhmed et al, 2019). The rational of its use is the stabilization of the lysosomal membrane, and reduction of the lymphocytic exudates (Raj et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in VAS scores before and after treatment were regarded as the main evaluation index. Based on previous reports (Fu et al, 2012; Raj et al, 2021), we assumed the average of VAS score after treatment would be 2.03 of the hydroxychloroquine group and 1.05 of the dexamethasone group, with a standard deviation of 1.15 and 1.25. The required sample size was calculated to be 42 patients per group, with 90% statistical power at a 2‐sided α of 0.05.…”
Section: Methodsmentioning
confidence: 99%